(3QSGdI aj Gdbhi GdCQHYIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd EbJVi JUfjai dgPg GdebGdI GdeMHI GdJi HjffG hZQVi GdHjGf Ydi Cf Gdbhi ai GdehVhY hCaYGdgG CQHYI KdGK efgG HGdPGJ s
(3BNQgG (B:s
(3aGdbhI GdJGHYI dg hGMOI agPG jLQi hjYfjfi ai eZdb HfGFg hgPg adjbWY GdcdGe ai ebGdJfG gPg Je GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3447/67) s
Keywords: (3GdadSaI hGdefWbs